Improving Students Learning Outcomes Through Mind Map in Human Reproductive System Topic in Natural Science Learning - Dewi, Aryani Kadarwati (Universitas Malikussaleh, 2019)
Natural science learning on the topic of the human reproductive system still gets a low score. That is due to the lack of use of learning media. The purpose of this study is to improve student learning outcomes through the use of mind maps in the topic of the human reproductive system. The research method used was classroom action research with the stages of pre-cycle, cycle 1, and cycle 2. The study was conducted in July 2019 and carried out at State Junior High School 1 South Tambun, Bekasi, Indonesia. The results showed that student learning outcomes increased from pre-cycle to cycle 1 (0.50) and from cycle 1 to cycle 2 (0.59) with a moderate gain score category. Whereas the pre-nuclear until cycle 2 (0.79) has a high gain score category. The use of mind maps is very useful because the reproductive system has many concepts that must be made simple. The conclusion is the use of mind maps can improve student learning outcomes on the topic of the human reproductive system